Educational Research Paradigms: From Positivism to Pluralism - Taylor, Peter; Medina, M. (Assumption College of Nabunturan, 2011)
In this paper we provide an overview of the characteristics of major educational research paradigms shaping contemporary educational research, ranging from the traditional positivist perspective to the latest multi-paradigmatic worldview. Our purpose is to orient students, faculty and beginning researchers to the newer paradigms that enable researchers to undertake uniquely powerful and insightful inquiries that contribute to transforming the landscape of education.